Self-efficacy and performance based on the statistics teaching methodology: Autoeficacia y desempeño en estadística a partir de la metodología empleada en el curso para estudiantes de psicología - González Franco, Verónica; Echeverría Castro, Sonia Beatriz; Sotelo Castillo, Mirsha Alicia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In order to compare the self-efficacy and performance in statistics of university students, before and after a traditional statistics course and one whit the problem-solving methodology, a quasi-experimental study was carried out on two intact groups of 84 and 115 students from psychology, respectively, applying a statistical self-efficacy sources test as a pre- and post-test, a mathematics exam before the course, and a statistics exam after the course. The results showed a significant difference in performance in statistics after the course, the experimental group had better resultsresults.